Sources of Stress among High School Teachers in the Occupied Territories - West Bank - Abed M. Assaf; Ahmad F. Jaber (My University, 1996)
The purposes of this study were; first, to identify the main Sources of Stress among secondary schools teachers in the occupied territories by Israel since 1967; second, to determine the importance of some demographic variables of (age, sex, social status, number of children, teacher qualifications, major, and years of teach experience) as independent variables, on teachers perception of the sources of stress, as dependent variables. The sample consisted of 115 respondents selected randomly from Nablus and Jerusalem districts in the West Bank. To collect the data, a scale of the sources of stress was constructed, validated, and administered to the subjects of the sample. The results of the study showed a relatively high level of stress among secondary school teachers. After testing, the null hypotheses by one-way ANOVA significant statistical mean differences were shown: 1. Among age groups on school factor [F (3:111) = 2.91, α = 0.05] 2. Between sex and school factor [F (1:113) = 6.06, α = 0.01] 3. Between sex and society factor [F (1:1113) = α - 0.05] 4. Among teachers of different qualifications on the administration factor [F (3:111)=3.19, α =0.05] 5. Among teachers of different qualifications on the school factor [F (3:111) = 3.04, α =0.05] 6. Among years of different teaching experience on the school factor [F (3:111) = 3.35, α =0.05] other subhypotheses were not statistically significant.
"مصادر الإجهاد النفسي لدى مدرسي المرحلة الثانوية في الوطن المحتل "الضفة الغربية